1977
DOI: 10.1002/bbpc.19770810320
|View full text |Cite
|
Sign up to set email alerts
|

Defects and Cation Diffusion in Magnetite (I)

Abstract: Using radioactive tracer Fe‐59 and measuring rest activities after sectioning, the tracer diffusivities of Fe in almost single crystalline magnetite Fe3‐ΔO4 have been measured as a function of temperature and oxygen partial pressure. The measured curves log DFe*/log pO2 all exhibit a minimum in the temperature range between 900°C and 1400°C in the homogeneity range of the magnetite. At sufficiently high oxygen partial pressures the slope ϱ log D Fe*/log pO2 is 2/3: at sufficiently low partial pressures it is —… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
4

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(73 citation statements)
references
References 4 publications
4
65
4
Order By: Relevance
“…At this oxygen pressure, the flux of O 2 molecules is 1.9ϫ10 17 The fact that the domain size is independent of the iron flux but decreases with increasing oxygen flux is quite surprising at first sight, but can be explained using general nucleation and growth theoretical arguments. We will start the discussion with the simpler case of the nucleation and growth of an elemental metal and follow the treatment of Villain et al 27 Adatoms are deposited at random with a flux F per unit area and time.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…At this oxygen pressure, the flux of O 2 molecules is 1.9ϫ10 17 The fact that the domain size is independent of the iron flux but decreases with increasing oxygen flux is quite surprising at first sight, but can be explained using general nucleation and growth theoretical arguments. We will start the discussion with the simpler case of the nucleation and growth of an elemental metal and follow the treatment of Villain et al 27 Adatoms are deposited at random with a flux F per unit area and time.…”
Section: Resultsmentioning
confidence: 96%
“…A comprehensive study of the bulk diffusion in Fe 3 O 4 has been performed by Dieckmann and Schmalzried. [17][18][19] They performed tracer diffusion experiments as a function of temperature and oxygen pressure. The main result was that diffusion occured via a defect mechanism and was therefore strongly dependent on the oxygen pressure (pO 2 ), because the formation of point defects depends on pO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the oxide, Fe 3 O 4 , with the spinel-type structure, Frenkeltype defects, which are pairs of cation vacancy and cation interstitial, are dominant at high temperatures, and then the diffusion coefficient of the cation, D C (m 2 /s), changes depending on the oxygen activity, a O 2 , as follows, [22][23][24] Dieckmann et al 22,23) showed that the cation diffusivity in Fe 3 O 4 at the temperature of 1 173 to 1 673 K was dominated by the iron-ion vacancy in the range of high oxygen activity, but by the iron-ion interstitial in the range of low oxygen activity. Also, Töpfer et al 25) showed that the defect concentration and the diffusion coefficient of cations, iron ion and chromium ion, depended on the composition, x, in (Fe 1Ϫx Cr x ) 3 O 4 (xϭ0, 0.1, 0.2, 0.3 and 0.4) at 1 473 K. The diffusion coefficients of iron ion and chromium ion changed with the oxygen activity in a similar manner.…”
Section: Defect Structures In (Fementioning
confidence: 99%
“…Many researchers have studied the cation tracer diffusion and jump frequency (Mossbauer spectroscopy) of magnetite in solid state [45][46][47][48][49][50][51][52][53][54][55][56] with partial pressure of oxygen (pO 2 ) and temperature. They found that diffusion of iron in magnetite lattice occurs by two different mechanisms-interstitial mechanism (at lower pO 2 and higher temperature) and vacancy mechanism (at higher pO 2 and lower temperature).…”
Section: Discussionmentioning
confidence: 99%